TRANSFORMASI PEMBELAJARAN MELALUI IMPLEMENTASI KURIKULUM MERDEKA: STUDI KASUS DI SD NEGERI SOKOWATEN BARU BANTUL YOGYAKARTA - Alwi Shihab Dly; Sulfiani, Sulfiani (Program Studi Manajemen Pendidikan Islam, 2024)
This study aims to evaluate the implementation of the Independent Curriculum at SDN Sokowaten Baru, Bantul, Yogyakarta, focusing on the adaptation process, challenges encountered, and the impact on learning quality. A qualitative case study approach was employed, using data collection methods such as observations, in-depth interviews with teachers and school principals, and document analysis. The findings reveal that the implementation of the Independent Curriculum has progressed well despite several challenges. Teachers demonstrated creativity and innovation in designing more relevant and contextual learning materials. Active student participation in the learning process significantly increased, positively impacting motivation and learning outcomes. However, challenges such as limited resources and insufficient understanding of the curriculum concept among some teachers were identified. The study concludes that the implementation of the Independent Curriculum at SDN Sokowaten Baru can be further optimized, offering the potential to serve as a model for other schools in Indonesia. These findings are expected to contribute strategically to future educational policy development.